2018
DOI: 10.1016/j.jtcvs.2018.04.098
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative cerebral hemodynamics from birth to surgery in neonates with critical congenital heart disease

Abstract: In neonates with TGA or HLHS, increasing cerebral oxygen extraction combined with an abnormal cerebral blood flow response during the time between birth and heart surgery leads to a progressive decrease in cerebral tissue oxygenation The results support and help explain the physiological basis for recent studies that show longer time to surgery increases the risk of acquiring white matter injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
38
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(45 citation statements)
references
References 37 publications
4
38
1
Order By: Relevance
“…9 There is accumulating evidence that the behavioural changes observed in children with CHD are related to hypoxic-ischemic white matter injury seen on brain MRI. 21 In children with Transposition of Great Arteries, the risk of developing white matter injury has been shown to increase with time between birth and surgery. 22 The underlying pathophysiology is likely related to the fact that cerebral oxygen extraction increases during the preoperative period in neonates with Transposition of Great Arteries, but without a concomitant increase in the oxygen delivery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…9 There is accumulating evidence that the behavioural changes observed in children with CHD are related to hypoxic-ischemic white matter injury seen on brain MRI. 21 In children with Transposition of Great Arteries, the risk of developing white matter injury has been shown to increase with time between birth and surgery. 22 The underlying pathophysiology is likely related to the fact that cerebral oxygen extraction increases during the preoperative period in neonates with Transposition of Great Arteries, but without a concomitant increase in the oxygen delivery.…”
Section: Discussionmentioning
confidence: 99%
“…22 The underlying pathophysiology is likely related to the fact that cerebral oxygen extraction increases during the preoperative period in neonates with Transposition of Great Arteries, but without a concomitant increase in the oxygen delivery. 21 Whether this is the same in children with Tetralogy of Fallot has to be explored, but overall it is well known that children with cyanotic CHD have an increased risk of impaired neurodevelopmental outcome through school age and into adolescence. 1,4,23 Of importance, it has been described that preoperative hypoxemia in infancy due to cyanotic CHD is likely to be associated with impaired attention functioning compared with acyanotic CHD and healthy children.…”
Section: Discussionmentioning
confidence: 99%
“…First, our inclusion criteria selected for the most critically ill neonates who required early cardiac repair, so that all neonates in our study were young, had complex congenital heart disease, and were exposed to prolonged CPB times (>120 min). Additionally, prior work has demonstrated that later surgical repair (or increased age at time of cardiac surgery) in neonates with congenital heart disease is associated with decreased hemoglobin saturation and increasing white matter injury [25,26]. Neonatal AKI occurrence may be similarly related to worsening oxygen delivery when surgical repair is delayed in these critically ill neonates.…”
Section: Discussionmentioning
confidence: 99%
“…Lynch and colleagues 4 suggest that preoperative patients may be particularly vulnerable because of an inability to decrease cerebral vascular resistance and increase cerebral blood flow in response to increasing oxygen demand, or to other stresses such as hypoxia or anemia. 4,23 Their previous work, however, has shown that preoperative neonates with either TGA or HLHS consistently demonstrate increased cerebral blood flow in response to hypercapnia, 8,24 indicating preservation of physiologic reserve in the cerebral vascular bed. Certainly, more work is necessary to clarify and reconcile these findings.…”
mentioning
confidence: 97%
“…9 BFI has also been found to correlate with cerebral blood flow measured by xenon-enhanced computed tomography in adults with head injury, 10 transcranial Doppler ultrasonography in premature infants, 11 and fluorescent microspheres in piglets. 12 The current study by Lynch and colleagues 4 includes 48 neonates, 24 with TGA and 24 with HLHS. Optical measurements were made once daily for a mean of 4 days and stopped once the patient went to surgery.…”
mentioning
confidence: 99%